Transformasi Digital dalam Manajemen Aparatur Sipil Negara: Implementasi Platform SmartASN - Shintia Yuniarti; Ahmad Muhardin Hadmar; Muchamad Zaenuri; Dyah Mutiarin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
Digital transformation is a critical need for modern governments to address the growing demands for fast, transparent, and efficient public services. This study examines the implementation of the SmartASN platform in driving the digital transformation of State Civil Apparatus (ASN) management. Employing a qualitative research approach with a narrative review methodology, the study systematically reviews and synthesizes secondary data collected from 2016 to 2022 on the digital transformation of ASN management. The Agile Governance theory guides the analysis. It focuses on three key aspects: 1) SmartASN Platform Governance, 2) Systematic and Adaptive Approaches in ASN Management, and 3) ASN Management in the Digital Age. The findings demonstrate that the SmartASN platform is instrumental in advancing ASN’s digital transformation, supporting Indonesia’s broader goals of creating a world-class bureaucracy. This is evidenced by Indonesia’s significant improvement in the E-Government Development Index (EGDI), which rose from 116 in 2016 to 77 in 2022. The study contributes to the academic understanding of digital governance by providing actionable recommendations to optimize the SmartASN platform and develop policies that support agile digital transformation. These insights highlight the potential of digital platforms in fostering innovation and enhancing adaptability in the public sector.